Protocol for the red reflex test: use in growth and development consultations - Araújo, Andréa Bárbara Santana de (2019)
The aim of this study was to elaborate a protocol that directs the nurses of the Basic Health Units of the municipality of Currais Novos/RN for the accomplishment of the Red Reflex Test to the children in the consultation of Growth and Development. Research type experience report, realized in two stages, the integrative review of findings and the protocol construction. Through the integrative literature review in the Lilacs, Scielo and Medline databases, with manuals and books, 10 references were analyzed between the years 2010 and 2017. Posteriorly, the protocol was elaborated for the accomplishment of the Red Reflex Test by the nurses, being the main criteria and techniques to be considered for the examination. It concluded that the protocol is of extreme importance and can be used in future training sessions and in the day-to-day care of nursing professionals, in order to promote better assistance to the ocular health of these individuals